A comparative study of single and double incision for L4/5 and L5/S1 double-level percutaneous interlaminar lumbar discectomy - Yingchuang Tang; Zixiang Liu; Hao Liu; Junxin Zhang; Xiaoyu Zhu; Zhonglai Qian; Huilin Yang; Haiqing Mao; Kai Zhang; Hao Chen; Kangwu Chen (Frontiers in Surgery, 2022)
ObjectiveThis study aims to investigate the clinical outcome of single and double incision for double-level percutaneous interlaminar lumbar discectomyMethodsA retrospective analysis was performed involving patients with L4/5 and L5/S1 double-level lumbar disc herniation who received percutaneous interlaminar lumbar discectomy (PEID) in our hospital from January 2017 to December 2020. These enrolled patients were divided into single- and double-incision groups, with 25 patients in each group. We compared the incision length, operation time, fluoroscopy times, and length of hospital stay between the two groups. Meanwhile, the postoperative visual analogue scale (VAS), Oswestry Disability Index (ODI), Japanese Orthopedic Association score (JOA), and modified MacNab standard were used to evaluate the outcomes of the patients within the two groups.ResultsIt showed that the single-incision group performed better than double-incision group in incision length, operation time, and fluoroscopy times (P < 0.001). The VAS score, JOA score, and ODI index in the two groups were significantly decreased at the time points of postsurgery, 1 month after surgery, and the last follow-up (P < 0.01), but there was no statistical significance between the two groups involving above parameters (P > 0.05). At the last follow-up, the excellent and good rates of MacNab efficacy in the two groups were 92% and 88%, respectively, but no significant difference was observed between the two groups (P > 0.05).ConclusionBoth the single- and double-incision approaches are effective and safe for managing L4/5 and L5/S1 double-level LDH. Single-incision PEID for treating L4/5 and L5/S1 double-segment lumbar disc herniation has advantages of less trauma, fewer intraoperative fluoroscopy times, and shorter operation time, as compared to double-incision PEID. However, the operation of double-segment LDH through a single laminar incision is difficult, the learning curve is steep, and professional skill is highly required. Importantly, the surgical indications should be strictly grasped.